2016
DOI: 10.1002/hep.28698
|View full text |Cite
|
Sign up to set email alerts
|

RNA helicase DEAD box protein 5 regulates Polycomb repressive complex 2/Hox transcript antisense intergenic RNA function in hepatitis B virus infection and hepatocarcinogenesis

Abstract: Chronic hepatitis B virus (HBV) infection is a major factor in hepatocellular carcinoma (HCC) pathogenesis by a mechanism not yet understood. Elucidating mechanisms of HBV‐mediated hepatocarcinogenesis is needed to gain insights into classification and treatment of HCC. In HBV replicating cells, including virus‐associated HCCs, suppressor of zeste 12 homolog (SUZ12), a core subunit of Polycomb repressive complex2 (PRC2), undergoes proteasomal degradation. This process requires the long noncoding RNA, Hox trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
160
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 122 publications
(171 citation statements)
references
References 51 publications
(121 reference statements)
11
160
0
Order By: Relevance
“…Given that the ATP binding domain and helicase motif that are important for DDX5 RNA binding and helicase activities are located at N-terminal domain, we wonder whether RNA binding and helicase activities are critical for its autophagy promotion function. We found that the DDX5-K144N mutant (25) that abolished ATPase activity and RNA binding activity also promoted autophagic flux the same as wild-type DDX5 (Fig. 4E).…”
Section: Ddx5 Is a P62-interacting Proteinmentioning
confidence: 65%
See 3 more Smart Citations
“…Given that the ATP binding domain and helicase motif that are important for DDX5 RNA binding and helicase activities are located at N-terminal domain, we wonder whether RNA binding and helicase activities are critical for its autophagy promotion function. We found that the DDX5-K144N mutant (25) that abolished ATPase activity and RNA binding activity also promoted autophagic flux the same as wild-type DDX5 (Fig. 4E).…”
Section: Ddx5 Is a P62-interacting Proteinmentioning
confidence: 65%
“…Previously, we reported that DDX5 regulated Polycomb repressive complex 2 (PRC2)‐mediated gene repression and modulated RNA‐protein complexes formed with HOTAIR. Hepatitis B virus (HBV)‐associated HCCs exhibited a strong negative correlation between DDX5 expression, pluripotency gene expression, and liver tumor differentiation . Recently, DDX5 has been reported to act as a reprogramming roadblock, regulating pluripotency gene expression through its role in miRNA processing .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This promotes PRC2-mediated gene repression (Zhang et al, 2016). RNA binding, but not ATP hydrolysis, is required for this activity (Zhang et al, 2016).…”
Section: Ddx5 and Ddx17 Regulate Lncrnps Formed By Lncrnas And Histmentioning
confidence: 99%